2021
DOI: 10.3389/fmicb.2021.737641
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Active Shewanella glacialimarina TZS-4T nov. Features a Temperature-Dependent Fatty Acid Profile and Putative Sialic Acid Metabolism

Abstract: Species of genus Shewanella are among the most frequently identified psychrotrophic bacteria. Here, we have studied the cellular properties, growth dynamics, and stress conditions of cold-active Shewanella strain #4, which was previously isolated from Baltic Sea ice. The cells are rod-shaped of ~2μm in length and 0.5μm in diameter, and they grow between 0 and 25°C, with an optimum at 15°C. The bacterium grows at a wide range of conditions, including 0.5–5.5% w/v NaCl (optimum 0.5–2% w/v NaCl), pH 5.5–10 (optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The host cells displayed a rod-shaped morphology, as previously described by Qasim et al [ 17 ]. In addition, a fraction of the cells expressed a single polar flagellum ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…The host cells displayed a rod-shaped morphology, as previously described by Qasim et al [ 17 ]. In addition, a fraction of the cells expressed a single polar flagellum ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 87%
“…Moreover, this study was carried out with undefined Zobell growth media based on aged Baltic Sea water [ 18 , 26 ]. We have previously shown that S. glacialimarina grows well in the defined 25% rMB [ 17 ], so we set out to recharacterize the infection characteristics in this new growth medium. First, we conducted infection cycle studies using an MOI ranging from 0.2 to 10 ( Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S-1 T was cultured routinely in TSA medium at 25 °C. All phenotypic tests were performed twice at different times on freshly prepared medium using standard methods as described previously [6,[34][35][36][37][38]. The Gram-staining was performed using a Gram-Stain kit (bioMérieux).…”
Section: Physiology and Chemotaxonomymentioning
confidence: 99%